2006
DOI: 10.1182/blood-2006-02-005397
|View full text |Cite
|
Sign up to set email alerts
|

Human SLP-65 isoforms contribute differently to activation and apoptosis of B lymphocytes

Abstract: The SH2 domain-containing leukocyte adaptor protein of 65 kDa (SLP-65) is the key effector for signaling downstream of the B-cell antigen receptor (BCR). SLP-65 controls not only B lymphopoiesis and humoral immunity but also possesses a yet poorly defined tumor suppressor activity that is lost in many cases of acute lymphoblastic leukemia. We found that the 2 isoforms of human SLP-65 are differentially involved in positive and negative B-cell signaling. Reconstitution experiments revealed that an atypical SH3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…5D). Interestingly, even though SLP65 is expressed in two isoforms, SCIMP interacted only with the longer form, which contains a binding site for the SH3 domain of Grb2 (18). This implies that binding of SLP65 to SCIMP may require the formation of a trimolecular complex involving Grb2.…”
Section: Resultsmentioning
confidence: 99%
“…5D). Interestingly, even though SLP65 is expressed in two isoforms, SCIMP interacted only with the longer form, which contains a binding site for the SH3 domain of Grb2 (18). This implies that binding of SLP65 to SCIMP may require the formation of a trimolecular complex involving Grb2.…”
Section: Resultsmentioning
confidence: 99%
“…Reintroduction of BLNK restored BLNK À/À pre-B-cell differentiation and inhibited their capacity (54). The long isoform of BLNK was also implicated in promoting BCR-induced apoptosis (55). On the other hand, BCAP participates in the PI3K/Akt pathway that promotes B-cell proliferation and survival and also leads to activation of JNK upon BCR engagement (27,49).…”
Section: Discussionmentioning
confidence: 99%
“…Luciferase and ␤-galactosidase activities were assayed and standardized as described by Brummer et al (39) for resting DT40 B cells and cells stimulated through their BCR for 6 h with M4 monoclonal antibody at a concentration of 2 g/ml. Where indicated, cells were pretreated one hour prior to BCR stimulation with SB202190 or SP600125 (Biomol) to inhibit p38 or JNK, respectively (29).…”
Section: Bcr-induced Ca 2ϩ Mobilization and Activation Of Luciferase mentioning
confidence: 99%
“…Indeed, recent studies showed that SLP-65 is capable of regulating MAP kinase activity in an inositol triphosphate/diacylglycerol-independent manner (25,29). These data suggest that phosphotyrosine-dependent and phosphotyrosine-independent processes cooperate to modulate SLP-65 signal output for early and late activation events.…”
mentioning
confidence: 92%